2018
DOI: 10.1016/j.energy.2018.08.087
|View full text |Cite
|
Sign up to set email alerts
|

Validated ejector model for hybrid system applications

Abstract: The aim of this work is the presentation of a new model for ejector performance calculation using a commercial tool. Due to the critical issues in recirculation performance, special attention is devoted to applications in hybrid systems based on high temperature fuel cells. The theoretical activity is supported by an experimental rig able to operate tests on ejectors at different operative conditions, with a layout similar to the fuel cell anodic recirculation. The model validation, operated considering experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…This issue is a main drawback as ejector highly influences the system performance, so that ad-hoc operation strategies and design procedures should be applied. In particular, Chen et al [29] studied suitable operation strategies; conversely, Ferrari et al [30] studied the design procedures. Chen et al [29] (anode/cathode ejector recirculation) studied different operation strategies for a hybrid solid oxide fuel cell-gas turbine: to ensure an appropriate operation strategy all the main system parameters should be adjusted to control the anode/cathode temperature difference and turbine inlet temperature.…”
Section: Current Achievements In Ejector-based Systems In Energy Conv...mentioning
confidence: 99%
See 1 more Smart Citation
“…This issue is a main drawback as ejector highly influences the system performance, so that ad-hoc operation strategies and design procedures should be applied. In particular, Chen et al [29] studied suitable operation strategies; conversely, Ferrari et al [30] studied the design procedures. Chen et al [29] (anode/cathode ejector recirculation) studied different operation strategies for a hybrid solid oxide fuel cell-gas turbine: to ensure an appropriate operation strategy all the main system parameters should be adjusted to control the anode/cathode temperature difference and turbine inlet temperature.…”
Section: Current Achievements In Ejector-based Systems In Energy Conv...mentioning
confidence: 99%
“…Chen et al [29] (anode/cathode ejector recirculation) studied different operation strategies for a hybrid solid oxide fuel cell-gas turbine: to ensure an appropriate operation strategy all the main system parameters should be adjusted to control the anode/cathode temperature difference and turbine inlet temperature. The regulation strategies rely on a precise modeling of ejector performances and, to this end, Ferrari et al [30] (anodic recirculation) presented a CFD model to predict ejector performances in a solid oxide fuel cell; the proposed approach was validated by experimental data and can be used to support the design and control of ejectors in fuel cell systems. It is worth noting that the use of an ejector in proton exchange membrane fuel cell need to consider gas management and water-control strategies.…”
Section: Current Achievements In Ejector-based Systems In Energy Conv...mentioning
confidence: 99%
“…They concluded that the diameter of the side‐branch secondary flow tube could significantly affect entrainment performance. Ferrari et al 46 employed a 3D CFD model to investigate the ejector performance at both design and off‐design conditions. Mazzelli et al 47 investigated the ejector numerically and experimentally to evaluate turbulence models and 3D effects.…”
Section: Numerical Simulation Methodsmentioning
confidence: 99%
“…They found that ε‐based models are more accurate at low pressures. Ferrari et al developed an ejector model for the solid oxide fuel cell (SOFC) system. The model is validated by their experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…They found that ε-based models are more accurate at low pressures. Ferrari et al 23 With the deepening of the research on ejector, some scholars have begun to study the transient process. Clou et al 24 proposed a 1D ejector transient model to investigate the performance in a pulse refrigeration system (PRS).…”
Section: Introductionmentioning
confidence: 99%